The impacts of housing conditions on physical and mental health: a critical mini-review informed by a rapid conversion of evidence from Alidoust and Huang (2021) - Simpson, Amelia; Filipe, Luís; Benedetto, Valerio; Hill, James (Frontiers in Environmental Health, 2024)
This article provides a summary and critical appraisal of the systematic review conducted by Alidoust et al. 1 regarding the various effects of housing on both physical and psychological well-being. We aim to discuss the review's findings against existing published evidence to draw out policy and practical implications. Our mini-review illuminates a wide range of housing-related factors which impact on health around which we draw evidence-based policy initiatives and implications, and outline avenues for future research. This mini-review is part of the wider Rapid Conversion of Evidence Summaries (RaCES) program which aims to critically appraise systematic reviews and highlight evidence-based policy and practice implications.